The objectifying gaze: a lacanian reading of Viet Thanh Nguyen’s The Refugees - Nurfarah Hadira Abdul Hadi,; Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the recent prevalence of white supremacist discourses in the United States, Asian Americans have unavoidably been subjected to xenophobic gazes and tendencies. The white gaze has traditionally enjoyed the privilege to objectify and fix the diasporic subject both racially and ethnically, foregrounding a relationality that naturalizes the immigrant as the inferior subject. The Vietnamese American writer Viet Thanh Nguyen recounts similar unsettling experiences and sufferings of the Vietnamese (refugees) in his debut short story collection The Refugees (2017). This essay seeks to explore the narrativesto outline the patterns of looking dynamics and stratified and interracial gaze operating among the characters. To this end, Lacanian theories of the gaze, the jouissance drive and the mirror stage are employed to examine the subtle nuances and complex mechanisms of looking relations that are instrumental in the development of Vietnamese characters. It is easily noticeable that the growing consciousness among the characters of their prescribed inferior position in the scopic order engenders in them feelings of anxiety and/or conflicting sexual impulses, or the jouissance drive. Nonetheless, the hierarchal gaze is not depicted throughout the collection as an essentialized and fixed phenomenon. Rather, some of the Vietnamese characters succeed to control, recodify and reassert the prevailing structural domination of the looking relations, and hence reclaim their agency and subjectivity in relation to the Other. It is concluded that Nguyen successfully upends the dominant discourses of representations in which the Americans’ centrality is eternalized while the Vietnamese’ is prescribed and nihilated.